An Analytical & Applied Study of Islamic Jurists Rule “Naqḍ al Istidlāl bi Ithbāt ‘annahu U’wwalu i’la al Maḥāl” - Farag, Saeed bin Ahmad Salih (Journal of Islamic and Religious Studies, 2021)
This research aims to prove the Islamic Jurists rule “Naqḍ al Istidlāl bi Ithbāt ‘annahu U'wwalu i’la al Maḥāl”. The main research problem lies in the “Maḥāl”, its limits, types, and ways of proving it. The researcher adopted the comparative-analytical inductive approach. After collection of the research material from the basic sources, explanation of Maḥāl, and analysis of the material was done by classifying it into rational and legal, and then the theoretical side on both applications was dropped to know the claim of the maḥāl for invoking analogy, and its fixations in Sharī’ah. The research concludes that this rule is used by scholars, and no one violated it. The legal impossible has ways by which it is known, i.e; every rational impossible is a legal impossibility, everything that contradicts the absolutes of the law is from the legal impossibility, and anything that contradicts a legal ruling that has been proven to be perpetuated is legally impossible. Moreover, all claims of impossibility of invoking analogy in Islamic law are neither proven nor valid, as well as all claims of impossibility of substitution in Sharī’ah.